2020
DOI: 10.4103/nmj.nmj_242_19
|View full text |Cite
|
Sign up to set email alerts
|

Routine histopathological analysis of the products of conception: Is there a value?

Abstract: Background: Spontaneous miscarriage is one of the two most common problems encountered in the first trimester of pregnancy. The value of histopathological analysis of products of conception (POC) obtained as a result is a source of controversy. The aim of this study is to evaluate the histopathological characteristics of suspected POC following the first-trimester miscarriage and determine the clinical value of such histopathological analyses. Materials and Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…POC with hydropic changes shows enlarged chorionic villi with pale edematous cores (5). POC with an Arias Stella reaction Compared to a study performed in Nigeria conducted by Hayi and Onyishi [25] reported normal POC constituted the most common histopathological diagnosis at 73 (68.2%); these results disagree with our results in normal POC, which was 59 (64.1%) in seronegative aborted women. Arias Stella reaction was eight (7.5%), which is higher than our results in seronegative aborted women with POC with Arias Stella reaction, which was three (3.2%); variation may be due to the geographical area and population differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…POC with hydropic changes shows enlarged chorionic villi with pale edematous cores (5). POC with an Arias Stella reaction Compared to a study performed in Nigeria conducted by Hayi and Onyishi [25] reported normal POC constituted the most common histopathological diagnosis at 73 (68.2%); these results disagree with our results in normal POC, which was 59 (64.1%) in seronegative aborted women. Arias Stella reaction was eight (7.5%), which is higher than our results in seronegative aborted women with POC with Arias Stella reaction, which was three (3.2%); variation may be due to the geographical area and population differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Products of conception (POC) passed spontaneously or evacuated surgically or medically are usually submitted to histopathological investigation, which entails a gross and microscopic examination of tissues received in the histopathology laboratory [25]. The predominant histopathological diagnosis was normal POC, which constituted 59 (64%) in seronegative women.…”
Section: Discussionmentioning
confidence: 99%